2016
DOI: 10.4103/0973-029x.190947
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 expression in normal oral epithelium, oral submucous fibrosis and oral squamous cell carcinoma

Abstract: Context:The epithelium atrophy, as the oral submucous fibrosis (OSMF) progresses, is believed to be an after effect of stromal fibrosis, hyalinization, decrease in vascularity and cellularity and is considered as “ischemic atrophy.” Due to hypoxia, caspase-3 get activation and subsequent decrease in viable cell count can occur.Aims and Objectives:To determine caspase-3 expression in various grades of OSMF and oral squamous cell carcinoma (OSCC) to find out whether upregulation of apoptosis is responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…This inhibition would permit an uncontrolled proliferation of keratinocytes with damaged DNA, whose tumorigenic mutations could lead to the oral cancer development. The reduced expression of caspase 3 in oral cancer tissues has been related to malignant transformation 34 . A recent investigation demonstrated that norepinephrine protected against apoptosis of mesenchymal stem cells by inhibiting the expression of caspase 3 via AKT/BCL-2 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition would permit an uncontrolled proliferation of keratinocytes with damaged DNA, whose tumorigenic mutations could lead to the oral cancer development. The reduced expression of caspase 3 in oral cancer tissues has been related to malignant transformation 34 . A recent investigation demonstrated that norepinephrine protected against apoptosis of mesenchymal stem cells by inhibiting the expression of caspase 3 via AKT/BCL-2 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of caspase 3 in oral carcinoma might be due to enhance or promote the apoptotic cascade. (Veeravarmal et al, 2016) reported low or absence of caspase 3 expression in oral squamous cell carcinoma. They suggested that caspase 3 expression tends to be decreased as the tumour progress.…”
Section: Resultsmentioning
confidence: 99%
“… 101 Stromal hypoxia leading to caspase-3 and -9 activation is the most plausible explanation for the downregulation of K-19 and the appearance of CYFRA21-1 in OSF. 102 , 103 CYFRA21-1 is thus a promising noninvasive proxy marker of hypoxia-initiated epithelial apoptosis and atrophy in OSF patients (Fig. 5a ).…”
Section: Alterations In the Expression Pattern Of Om-scms In Osf Opmmentioning
confidence: 99%